Campylobacter jejuni Modulates Reactive Oxygen Species Production and NADPH Oxidase 1 Expression in Human Intestinal Epithelial Cells - Geunhye Hong; Cadi Davies; Zahra Omole; Janie Liaw; Anna D. Grabowska; Barbara Canonico; Nicolae Corcionivoschi; Brendan W. Wren; Nick Dorrell; Abdi Elmi; Ozan Gundogdu (Cellular Microbiology)
Campylobacter jejuni is the major bacterial cause of foodborne gastroenteritis worldwide. Mechanistically, how this pathogen interacts with intrinsic defence machinery of human intestinal epithelial cells (IECs) remains elusive. To address this, we investigated how C. jejuni counteracts the intracellular and extracellular reactive oxygen species (ROS) in IECs. Our work shows that C. jejuni differentially regulates intracellular and extracellular ROS production in human T84 and Caco-2 cells. C. jejuni downregulates the transcription and translation of nicotinamide adenine dinucleotide phosphate (NAPDH) oxidase (NOX1), a key ROS-generating enzyme in IECs and antioxidant defence genes CAT and SOD1. Furthermore, inhibition of NOX1 by diphenylene iodonium (DPI) and siRNA reduced C. jejuni ability to interact, invade, and intracellularly survive within T84 and Caco-2 cells. Collectively, these findings provide mechanistic insight into how C. jejuni modulates the IEC defence machinery.